Academic dishonesty and misconduct in online programs and online exams – an Australian study - E., Smith,; L, Clarke, (IJRDO- Journal of Educational Research, 2017)
Now days an increasing number of universities are offering online degrees.In Australia most universities offer online degrees, however, this study will take a closer lookat an organisation which offers the largest selection of online courses. For the purposed of thisstudy the organisation will be referred to as “online degree providers” (ODP).Along with this new method of completing degrees comes new forms of academic dishonestyand misconduct. Academic dishonesty and misconduct among students is not a newphenomenon.According to Rokavski and Levy (2007), cheating in general at universities is growing at arampant rate. Researchers such as Stack (2015) find that academic dishonesty and misconductat universities nowadays is even more prevalent than in the past due to technological advances,relatively scarce resources and understaffing at universities (Treviño and Butterflied, 1999;Maslen, 2003; Stack, 2015). The most common and widely used notion of academic dishonestyand misconduct at universities is copying and/or cheating on an exam (Teixeira and Rocha,2010).Hence, these global findings also apply to Australian universities. Therefore, this paperexamines academic dishonesty in relation to online exams in Australia. Even though this paperconsiders academic dishonesty broadly, the focus of the paper is on cheating in online exams.This paper contributes to the limited research literature on academic dishonesty and misconductin online programs and online exams at Australian universities by taking a close look at whatacademic dishonesty and misconduct is and how it may be minimised.